2014
DOI: 10.1155/2014/345105
|View full text |Cite|
|
Sign up to set email alerts
|

Antiaging Properties of a Grape-Derived Antioxidant Are Regulated by Mitochondrial Balance of Fusion and Fission Leading to Mitophagy Triggered by a Signaling Network of Sirt1-Sirt3-Foxo3-PINK1-PARKIN

Abstract: It was proposed that resveratrol, a polyphenolic antioxidant and a calorie restriction mimetic could promote longevity but subsequent studies could not prove this. The original proposal was based on the fact that a grape-derived antioxidant could activate the antiaging gene Sirt1. Most studies agree that indeed grape activates Sirt1, but a question remains whether Sirt1 is the cause or consequence of resveratrol treatment. Subsequently, mitochondrial Sirt3 was found to be activated. The present study on ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
102
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(106 citation statements)
references
References 40 publications
(66 reference statements)
1
102
0
1
Order By: Relevance
“…Mukherjee et al have demonstrated that longevinex (modified SIRT1 activator) improves cardiac performance and decreases infarct size in hearts subjected to 30 min of ischemia followed by 2 h reperfusion while increases survival factors expression and theses effects were accompanied by enhanced SIRT3 expression (30). In another study resveratrol, SIRT1 activator, protected the heart against ischemia reperfusion injury via activation of Foxo3a subsequent to SIRT3 activation which increased intracellular concentration of glutathione in the heart (31).…”
Section: Discussionmentioning
confidence: 99%
“…Mukherjee et al have demonstrated that longevinex (modified SIRT1 activator) improves cardiac performance and decreases infarct size in hearts subjected to 30 min of ischemia followed by 2 h reperfusion while increases survival factors expression and theses effects were accompanied by enhanced SIRT3 expression (30). In another study resveratrol, SIRT1 activator, protected the heart against ischemia reperfusion injury via activation of Foxo3a subsequent to SIRT3 activation which increased intracellular concentration of glutathione in the heart (31).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence confirms that a tight relationship exists between SIRT1 and SIRT3. Resveratrol, a polyphenolic antioxidant and a calorie restriction mimetic, exerts its anti‐aging effects by potentiating a signal transduction cascade consisting of SIRT1/SIRT3‐FOXO3a‐PINK1‐PARKIN . Liu et al.…”
Section: Discussionmentioning
confidence: 99%
“…FOXO3a, a transcription factor, is an important target of SIRT1. SIRT1 deacetylates FOXO3a, triggers transcription of FOXO3a-dependent stress resistance genes, and contributes to increased longevity (Das et al, 2014). However, recent research has found that curcumin reduces macrophage lipid accumulation in LDL receptor knockout mice fed a high-fat diet for 4 months through the SIRT1-FOXO3a axis.…”
Section: Discussionmentioning
confidence: 99%